(untitled) (Педагогіка вищої та середньої школи, 2006)
Clause is devoted to questions of logic communication intonational "the theories of a history" B. Astaffiev and his rules musical of didactis. which have continuation and recognition in modem worts musicologists of Ukraine and outside of her.